Characterization and morphological study of microbes in treated palm oil mill effluents - Rosdi, Afiqah; Dahalan, Farrah Aini; Zhang Zhan, Loh; Babakhani, Peyman; Shams, Shahriar (Environmental and Toxicology Management, 2022)
Palm oil mill effluent (POME) is wastewater generated by palm oil milling. Due to its extremely polluting qualities, it must be treated before being discharged into the water course. This study was aimed to evaluate the bacterial growth of raw and treated POME as well as identifying indigenous microorganisms by determining the morphological characteristics of bacteria that were found in the POME. The bacterial growth was identified by bacterial enumeration of colony forming units (CFU). Besides, the morphological identification of bacteria was determined by using gram staining. The results show the best bacterial growth curve is from serial dilution factor of 10-6 with a total of 2.24 x 10-6 CFU/mL in raw POME and optimum growth on day seven. While for the treated POME, the total is 1.97 x 10-6 CFU/mL and recorded the optimum growth on day ten of incubation. The growth curve indicates the number of colonies in raw POME is higher than treated POME. It concluded that treated POME still has the bacteria although it has been treated. Apart from that, from the morphological identification by gram staining, the bacteria were Bacillus cereus, Bacillus subtilis, Staphylococcus aureus and Micrococcus luteus. From a gram staining, this research obtained all gram positive in purple colour from the POME samples. Two of them in treated POME were in Bacillus shape while the other two from raw and treated POME were in coccus shape, respectively.